1997
DOI: 10.1079/bjn19970132
|View full text |Cite
|
Sign up to set email alerts
|

Digestion and metabolism of dietary fat in farm animals

Abstract: ~~Fat digestion and metabolism differ widely between animal species. In ruminants, dietary fats are hydrogenated in the rumen before intestinal absorption so that absorbed fatty acids (FA) are more saturated than dietary FA. In non-ruminants, intestinal FA digestibility depends on the level of saturation of dietary FA. Fat supplementation of the diet of cows decreases milk protein and has a variable effect on milk fat, depending on the source of dietary lipids. When encapsulated lipids are used, the linoleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
176
3
20

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(219 citation statements)
references
References 101 publications
20
176
3
20
Order By: Relevance
“…As expected, unsaturated FA were better absorbed than were SFA, and stearic acid was less well absorbed than was palmitic acid, because as unsaturation increases, digestibility is increased, and as the FA chain length increases, digestibility is reduced (Doreau and Chilliard, 1997). In this sense, SN, due to its high unsaturated FA content, showed the greatest total FA apparent absorption and, therefore, the greatest digestible energy.…”
Section: Digestibility Balancesupporting
confidence: 60%
“…As expected, unsaturated FA were better absorbed than were SFA, and stearic acid was less well absorbed than was palmitic acid, because as unsaturation increases, digestibility is increased, and as the FA chain length increases, digestibility is reduced (Doreau and Chilliard, 1997). In this sense, SN, due to its high unsaturated FA content, showed the greatest total FA apparent absorption and, therefore, the greatest digestible energy.…”
Section: Digestibility Balancesupporting
confidence: 60%
“…Moreover, no differences (P > 0.05) were found in carcass weight, conformation, fatness or pH 24 h after slaughter (Table 3). It is generally accepted that including unsaturated fats in ruminant rations leads to a decrease in the digestion of structural carbohydrates in the rumen, and that the reduction is less when protected fats are used, such as calcium soaps or hydrogenated fats (Doreau and Chilliard, 1997). A lower productive output with the SOY treatment, compared with PALM and OLI, was therefore to be expected.…”
Section: Resultsmentioning
confidence: 99%
“…In a review of data on the use of fats in steer fattening, Clinquart et al (1995) found that incorporation levels below 5% do not affect ruminal digestion or productive output, irrespective of the type of fat used or how the fats are pre-treated. Doreau and Chilliard (1997) indicated that the reduced digestibility of organic matter when unsaturated fats are added is due to a poorer utilisation of the fibrous fraction, without modification of starch digestion. It has been demonstrated that lipids have a negative effect on bacterial growth.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen was assumed to be produced when OM was fermented to Ac and Bu, and used during production of Pr and Va. Since two of the three trials used high-fat diets and the FA concentration varied substantially between diets, the amount of H 2 available for CH 4 production was corrected for biohydrogenation, assuming hydrogenation rates of 75% for C18:1, 80% for C18:2 and 92% for C18:3 (Weisbjerg et al, 1992;Doreau and Chilliard, 1997). After this correction, it was assumed that all residual H 2 was converted to CH 4 (i.e.…”
Section: Calculationsmentioning
confidence: 99%